Analisis Faktor-Faktor Yang Mempengaruhi Niat Penggunaan E-Wallet Dana - Nurdiansyah, Fadlan Hasan; Ahmadi, Mirzam Arqy (Jurnal Serambi Ekonomi dan Bisnis, 2024)
The development of digital technology has accelerated the adoption of e-wallets as a modern payment method in Indonesia. DANA is one of the increasingly popular e-wallet platforms, yet certain challenges hinder its full adoption. This study aims to analyze the factors influencing the intention to use the DANA application, such as perceived usefulness, ease of use, social influence, and service quality. The research employs a qualitative descriptive method through a literature review approach to gain theoretical and empirical insights into the adoption of e-wallet technology. The findings reveal that perceived usefulness and ease of use significantly enhance users' intentions. Furthermore, social influence, including recommendations from close contacts and trends on social media, motivates new users to try DANA. Consistent and responsive service quality reinforces the intention to use the application repeatedly. Understanding these factors enables DANA to develop more effective strategies for boosting adoption and user loyalty in the competitive e-wallet market.